MANAJEMEN FISIOTERAPI PADA PASIEN POST ORIF RECONSTRUCTIONS ET CAUSA MALUNION TIBIAL PLATEAU FRACTURE SINISTRA: CASE REPORT - Pasya, Muhammad Sena Nurrahman; Mustiko, Prihantoro Larasati; Rahayu, Umi Budi (Prosiding University Research Colloquium, 2024)
Malunion Tibial plateau fractures is a popular term used to describe fractures that occur in the upper joint of the tibia. This injury is common and accounts for approximately 1% of all fractures in the adult population. Tibial plateau fractures have a substantial impact on patients' lives, resulting in decreased quality of life and decreased participation in sports activities. Rehabilitation plays an important role in patients with Sinistra Tibial Plateau Fracture Malunion because it can help in restoring mobility, strength and function of the fractured extremity. Post ORIF Fracture Tibial Plateau conditions cause pain, edema, decreased joint range of motion, muscle weakness, and decreased ability to perform functional activities. The implementation of the physiotherapy program in this case aims to determine the effect of providing physiotherapy intervention in the form of ankle pumping exercise in reducing pain and reducing edema, active assisted exercise in increasing muscle strength, and walking using a walker to optimize the functional activity of Post ORIF Fracture Tibial Plateau patients. This research method was carried out directly on 1 respondent with the condition Post ORIF Fracture Tibial Plateau Sinistra by giving physiotherapy 4 therapy sessions to Mr. IA (32 years). After the ankle pumping exercise therapy, active assisted exercise, and walking using a walker with an intensity of 8 repetitions, 3 sets were carried out for 4 days (1 session per day). The results of four exercise sessions showed a decrease in pain measured using the Numeric Pain Rating Scale, a decrease in edema using the Meter Line, an increase in muscle strength measured using Manual Muscle Testing, and an increase in functional activity measured using the Barthel Index. The conclusion was that the physiotherapy program in the case of Post ORIF Fracture Tibial Plateau Sinistra was proven to be able to reduce pain, edema, increase muscle strength and increase functional activity.